Sistem Informasi Notifikasi Imigarasi Berbasis Web dan SMS Gateway - Fajriaty, Siti; Arhami, Muhammad; Nasir, Muhammad (Politeknik Negeri Lhokseumawe, 2023)
Information becomes an absolute necessity for every organization, both organization, government and private. The overall activities of the organization basically require information. Therefore, information becomes a very important part to support the work process in an office or agency. One important source of information that can support administrative and bureaucratic activities is data processing. Good data processing that can support administrative activities is very useful for agency progress. Therefore, it is necessary to compile a system so that the implementation and processing of data can be seen clearly and the transparency reflected in the series of systems. Visa and Permit Information System Stay at the Immigration Office. Therefore all forms of company documents that enter or leave must be stored in the visa application system and the online residence permit, and controlled, is well organized to facilitate the search for application status information. This system can improve the ease and smooth operation of the system, so that it can provide high quality services to the community. Also internally it is increasingly encouraging to increase work productivity in the delivery of information to the applicants via SMS. The results show that the Immigration Office has used a notification information system to inform visa citizens to foreign citizens and passport notifications to the Lhokeumawe community Keywords: handphone, PC, information system, Notification, Immigration, SMS Gateway, PHP